Challenges and Remedies for Research Investment in Tertiary Institutions: Insights from Nigeria: Tantangan dan Upaya untuk Investasi Riset di Institusi Pendidikan Tinggi: Wawasan dari Nigeria - Jacob, Ogunode Niyi; Atoshi, Mikyitsabu Ago; Johnson, Gani (Universitas Muhammadiyah Sidoarjo, 2023)
In this study, we investigate the factors contributing to the inadequate investment in research programs within Nigerian tertiary institutions. Employing secondary data from both printed and online sources, we identify key issues such as the lack of political commitment in implementing research funding policies, declining national revenue, corruption, security concerns, limited private sector involvement, competition from other economic sectors, revenue source limitations, and high debt servicing as primary drivers of this problem. To address these challenges, our recommendations include the implementation of research funding policies, economic diversification, the establishment of effective monitoring and evaluation mechanisms for research funds, the creation of additional sources of research funding, and greater private sector engagement in supporting research endeavors across the nation. This study provides valuable insights into the challenges faced by the Nigerian higher education sector in fostering research excellence and offers practical solutions to enhance research investment for sustainable development. Highlights: Inadequate Funding: Insufficient financial support hinders research program growth. Political Will: Lack of commitment from policymakers affects research funding policy implementation. Private Sector Engagement: Greater involvement of private industries can boost research investment in Nigeria's tertiary institutions. Keywords: Research Investment, Tertiary Institutions, Nigeria, Funding Policy, Private Sector Participation